A new auxetic structure with significantly reduced stress concentration effects. (5th July 2019) - Meena, Kusum; Singamneni, Sarat
Abstract: Auxetic structures exhibit certain abnormal mechanical responses such as negative Poisson's ratios, mainly through the intertwined deformation attributes of inter-connected members of macro structural forms. Considering the relative ease of achieving complex forms with the advent of the additive manufacturing technologies, there is a renewed interest in auxetic structures, as the already established as well as new structural shapes are physically produced and tested to ascertain the theoretical predictions. While the focus was mostly around the auxetic responses, the stress distribution patterns and in particular the stress concentration effects were mostly neglected. This paper fills this gap, evaluating the stress concentration aspects of a standard re-entrant auxetic structure. A new structure is designed and proven to be less stressed in comparison with the re-entrant form commonly reported in the literature by means of analytical, experimental, and numerical results. The new structure proposed has proved to be more auxetic up to 15% of the external strain and with Poisson's ratios up to −2.5. Graphical abstract: Unlabelled Image Highlights: The re-entrant cells underwent strut detachment, while the S-structures showed no evidence of the formation of any cracks. The stress concentration effects more than doubled in the re-entrant unit cells compared to the S- unit cells The S-structure resulted in a negative Poisson's ratio as high as 2.5 as against a negative maximum of 1.2 in the case of the re-entrant one. The re-entrant and the S structures remained auxetic within 5% and 15% of the macroscopic applied strains respectively